Authorea
DOI: 10.22541/au.158447922.28650439
|View full text |Cite
|
Sign up to set email alerts
|

Advancing biodiversity assessments with environmental DNA: Long-read technologies help reveal the drivers of Amazonian fungal diversity

Abstract: Fungi are a key component of tropical biodiversity. Due to their inconspicuous and largely subterranean nature, they are however usually neglected in biodiversity inventories. The goal of this study was to identify the key determinants of fungal richness, community composition, and turnover in tropical rainforests. We tested specifically for the effect of soil properties, habitat, and locality in Amazonia. For these analyses, we used high-throughput sequencing data of short and long reads of fungal DNA present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
1
8
1
Order By: Relevance
“…Among the eukaryotes, we found a higher proportion of fungi in the Juruá substrates than previously documented elsewhere in Amazonia (Ritter, Zizka, et al, 2019). Whereas Ritter, Dunthorn, et al (2020) found fewer fungi in várzea than in other environments, we found more fungi in várzea than in the adjacent terra firme, most of which were saprotrophs (Appendix S4: Figure A2). Singer et al (1983) hypothesized that ectomycorrhizal fungi increase the ability of their host plants to acquire nutrients and water in low‐fertility soils, such as in the Amazonian sandy‐soil ecosystems.…”
Section: Discussioncontrasting
confidence: 77%
“…Among the eukaryotes, we found a higher proportion of fungi in the Juruá substrates than previously documented elsewhere in Amazonia (Ritter, Zizka, et al, 2019). Whereas Ritter, Dunthorn, et al (2020) found fewer fungi in várzea than in other environments, we found more fungi in várzea than in the adjacent terra firme, most of which were saprotrophs (Appendix S4: Figure A2). Singer et al (1983) hypothesized that ectomycorrhizal fungi increase the ability of their host plants to acquire nutrients and water in low‐fertility soils, such as in the Amazonian sandy‐soil ecosystems.…”
Section: Discussioncontrasting
confidence: 77%
“…Many studies sampling fungal diversity in under‐explored environments have shown that they contain species new to science. In the tropics, Ritter et al., (2020) recently showed that a single teaspoon of Amazonian soil may contain as many as 400 Operational Taxonomic Units of fungi, roughly equivalent to genetically separate species. But undescribed species are also found in temperate and glacial regions, as recently shown by the study surveying 130 locations in Denmark in which over 100 new species of fungi were described (Velux Foundation, 2020) and new discoveries from the Antarctic Peninsula (Ogaki et al., 2020).…”
Section: Fungal Culture Collectionsmentioning
confidence: 99%
“…Molecular data already frequently contribute towards creating biodiversity inventories (Taberlet et al 2018, Ruppert et al 2019) and rapid biodiversity assessments at local scales (eDNA and meta‐barcoding, Yu et al 2012, McClenaghan et al 2020) including baseline flora and fauna identification (Hofreiter et al 2001). They are also routinely employed for overcoming sampling gaps in cryptic taxa and remote areas (Barratt et al 2017, 2018, Lentendu et al 2018, Ritter et al 2019a, b, 2020), understanding gene–environment interactions (Ritter et al 2018, Zinger et al 2019), species interaction (Doliwa et al 2021, Ritter et al 2021) and cross‐taxonomic analyses of genetic diversity and population structure (Miraldo et al 2016, Gratton et al 2017, Theodoridis et al 2020). Recent applications have highlighted the use of molecular data for biodiversity monitoring (Flanagan et al 2018, Hunter et al 2018) and the response to stressors and conservation measures (Beermann et al 2018, Zizka et al 2020a, b), with a number of programs instigated by several stakeholders to monitor genetic diversity (e.g.…”
Section: Discussionmentioning
confidence: 99%